An Analysis of Students’ Vocabulary Mastery by Using Word Chain Game at Basic Level of AVON English School Kepung Pare - Novi Rina Dewi; Alfany Fardan Syahuma (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2022)
This thesis aims to analyze the implementation of word chain game to the students’ vocabulary mastery and to analyze the student’s responses toward the word chain game in their vocabulary mastery at the basic level of AVON English School. This research is a type of qualitative (field research), this research is designed to measure the implementation of Word Chain Game in the mastery of English vocabulary. Here Researcher collect data from the field by investigating directly in the field to find various relevance to this research. While the approach used in this research is qualitative approach. Based on the findings of research and discussion on Learning, the students enjoy and have fun in learning English vocabulary. This game helps them recall their memories about the vocabulary they have known before, enhance their mastery vocabulary, and helps them find the clue to tell any vocabularies. The students found it easier to learn vocabulary in the classroom. The students were more and enthusiastic to join the meaningful and contextual activity. They learned to share and co-operate each other in communicative activity in the classroom. After finding and analyzing the data of this study, it can be concluded that Word Chain Game as one of the games in English teaching learning process can be applied to the mastery of English vocabulary and it has a positive influence on vocabulary mastery in the learning. Therefore, Word Chain Game helps the students feel confident in saying any English vocabularies and avoid the tedious situation in English teaching learning process. Keywords : Word Chain Game, Vocabulary Mastery, Basic Level